Enacting Metaphors in Systemic Collaborative Therapy - Rucińska, Zuzanna; Fondelli, Thomas (Frontiers in Psychology, 2022)
What makes metaphors good therapeutic tools? In this paper we provide an answer to this question by analyzing how metaphors work in systemic collaborative therapeutic practices. We look at the recent embodied, enactive and ecological proposals to metaphors, and provide our own, dialogical-enactive account, whereby metaphors are tools for enacting change in therapeutic dialogues. We highlight the role of enacting metaphors in therapy, which is concerned with how one uses the metaphors in shared process of communication. Our answer is that metaphors serve as good tools for connecting to action words, through which the client's embodiment and agency can be explored. To illustrate our view, we analyze two examples of enacting metaphors in therapeutic engagements with adolescents. Our enactive proposal to metaphors is different from others as it does not rely on engaging in explicit performances, but stays within a linguistic dialogue. We take metaphoric engagement as an act of participatory sense making, unfolding in the interaction. This insight stems from enactive ways of thinking about language as a process accomplished by embodied agents in interaction, and seeing talking also as a form of doing.